ANALYSIS OF ROB FLOOD MITIGATION IN BAGAN DELI VILLAGE, MEDAN BELAWAN DISTRICT, MEDAN CITY - Abdullah Basalamah; Ahmad Perwira Mulia; Gina Cynthia Raphita Hasibuan (Bulletin of Engineering Science, Technology and Industry, 2025)
Bagan Deli Village, located in Medan Belawan District, is a coastal area that is vulnerable to tidal flooding due to rising sea levels and land subsidence. The land subsidence and speed of land subsidence that occurred in Bagan Deli Village, Medan Belawan District, amounted to 6.50 cm. This problem has a significant impact on the social, economic, and environmental lives of the local community. This study aims to analyze tidal flood mitigation strategies that can be applied to reduce its impact. The method used is descriptive qualitative with a field study approach, interviews, and documentation. The results of the analysis show that the construction of drainage channels, river dredging, raising floors, infiltration wells, water gates, socialization and formation of working groups, planting mangroves, pump houses, and stilt houses are effective mitigations. This study provides strategic recommendations for local governments and related parties in formulating appropriate and sustainable tidal flood mitigation policies.